PENGEMBANGAN MODEL SUPERVISI AKADEMIK TEKNIK MENTORING BAGI PEMBINAAN KOMPETENSI PEDAGOGIK GURU KELAS - Merukh, Nehtry; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2016)
This research aimed to describe (1) Implementation of principal supervision at TunasÂ Gloria Elementary School, Kupang; (2) Problems in the implementation of principalÂ supervision at Tunas Gloria Elementary School, Kupang; and (3) Creating of the academicÂ supervision models of pedagogic competence guidance mentoring technique for homeroomÂ teacher. This research is R & D (Research and Development) by following steps ofÂ development according to Sugiono (2009). Questionnaires, interviews and documentationÂ studies were used as data collection techniques. Delphie technique was used as modelÂ validation. Results of research showed that (1) Implementation of principal supervision hasnot been performed according to principles of supervision performance, (2) problems in theÂ implementation of principal supervision i.e. a written planning has not been made; purposesÂ of supervision has not been constructed according to the needs of teachers; guidance forÂ supervision performance was still insufficient; time demand for principal; the performance ofÂ supervision was only adjusted to the supervision of supervisor; the comprehension fromÂ principalin performing of evaluation. The final result was in the form of academicÂ supervision models of pedagogic competence guidance mentoring technique for homeroomÂ teacher that consists of 4 stagesâplanning, performance, evaluation and follow-up.